Język pracowników służb specjalnych w Polskiej Rzeczpospolitej Ludowej i w Bułgarskiej Republice Ludowej (na przykładzie analizy teczek TW „Bolek” i TW „Sabina”) - Mazurkiewicz-Sułkowska, Julia (Języki specjalistyczne w komunikacji interkulturowej, 2020)
Releasing declassified files, reports, denunciations and other Communist-era secret service documents in the former socialist countries raises great controversies and emotions. The so-called “teczki” become an element of political maneuvering and power games. Reports from the informants and collaborators are usually the object of consideration for historians and archivists alike. However, there are virtually no linguistic analyses that characterize them. The paper is an attempt to investigate the language of secret service employees from a comparative perspective based on two collections of notes from Poland and Bulgaria.